Illumina MiSeq sequencing reveals the key microorganisms involved in partial nitritation followed by simultaneous sludge fermentation, denitrification and anammox process. (May 2016) - Wang, Bo; Peng, Yongzhen; Guo, Yuanyuan; Zhao, Mengyue; Wang, Shuying
Graphical abstract: Highlights: First systematically investigated PN-SBR/SFDA using high-throughput sequencing. Observed long-term stable partial nitrification in the PN-SBR. Identified key functional microorganisms contributing to simultaneous SFDA. Abstract: A combined process including a partial nitritation SBR (PN-SBR) followed by a simultaneous sludge fermentation, denitrification and anammox reactor (SFDA) was established to treat low C/N domestic wastewater in this study. An average nitrite accumulation rate of 97.8% and total nitrogen of 9.4 mg/L in the effluent was achieved during 140 days' operation. The underlying mechanisms were investigated by using Illumina MiSeq sequencing to analyze the microbial community structures in the PN-SBR and SFDA. Results showed that the predominant bacterial phylum was Proteobacteria in the external waste activated sludge (WAS, added to the SFDA) and SFDA while Bacteroidetes in the PN-SBR. Further study indicated that in the PN-SBR, the dominant nitrobacteria, Nitrosomonas genus, facilitated nitritation and little nitrate was generated in the PN-SBR effluent. In the SFDA, the co-existence of functional microorganisms Thauera, Candidatus Anammoximicrobium and Pseudomonas were found to contribute to simultaneous sludge fermentation, denitrification and anammox.